Decolonising the African university again - Waghid, Y. (South African Journal of Higher Education, 2021)
The notion of the African university ought to be decolonised on the grounds that decolonisation enhances humanisation and rehumanisation, as well as cosmopolitan pluriversalism. This article argues that unless the university takes its task to liberate, resist, and advance cosmopolitan ideals seriously, the decolonisation of the African university will remain elusive.